DETERMINANTS OF HOUSEKEEPING EMPLOYEE PERFORMANCE AT TANDJUNG SARI HOTEL SANUR: WORK MOTIVATION AS A MEDIATOR - Putu Ayu Krisna Listya Dewi; I Gede Riana (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyze the effect of management support on employee performance with work motivation as a mediating variable at Tandjung Sari Hotel Sanur. The population in this study were all housekeeping employees of Tandjung Sari Hotel Sanur. The respondents of this study were 45 housekeeping employees who were determined using the non-probability sampling method with saturated sampling techniques. Data were collected through questionnaires and interviews that were distributed directly to each housekeeping employee of Tandjung Sari Hotel Sanur. Data were analyzed using the PLS-SEM (Partial Least Square Structural Equation Modeling) technique with the help of the Smart PLS 4.1 application. The results showed that management support had a positive and significant effect on employee performance, where the work motivation variable was able to mediate the effect of management support on housekeeping employee performance in a complementary partial mediation. The implication of this study is the need for management to provide strong support to employees to increase work motivation, which in turn will improve employee performance. This study contributes to understanding the internal dynamics of organizations in the context of the hospitality industry, especially in increasing productivity and service quality through effective work motivation management.